Level of Academic Stress for Students of Guidance and Counseling at Semarang State University during the Pandemic - Octasya, Tivanny; Munawaroh, Eem (Universitas Negeri Yogyakarta, 2021)
Academic stress is a subjective perception of an academic condition or a response experienced by students in the form of negative physical reactions, behaviors, thoughts, and emotions that arise due to school or academic demands. During a pandemic Covid 19 most of earning activities becomes online. The aim of this research is to determine the level of academic stress among students in Guidance and Counseling Department, Semarang State University during the pandemic. The method used is descriptive qualitative research. This research conducted interviews to collect data by using purposive sampling. The results show that students experience symptoms of academic stress symptoms that affect their physical, emotional, behavioral, and thoughts as well as several factors that influence academic stress both in themselves (internally) and in the environment and circumstances (externally). The conclusion of this study is the respondents' stress level is quite high or increases when they get assignments from the lecturers.